2022
DOI: 10.3384/rela.2000-7426.3513
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of intrinsic values in education for older adults: insights from a Swedish senior university

Abstract: This study aims to acquire more knowledge about the meaning of intrinsic values in or­ganised post-work non-formal educational activities for older adults. Observations and focus group interviews were conducted at a senior university in Sweden. John Dewey’s concept of experi­ence and theory of value are used to facilitate a deeper under­standing of the in­trinsic values that were identified. The results of the study demonstrate what intrinsic values in education for older adults can be, as well as how they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(42 reference statements)
1
0
0
Order By: Relevance
“…Similarly, lifelong learning has been associated with the reduction of cognitive decline in older adults, even with short participation in cognitively stimulating activities [40]. Several studies have shown that computer use increases social interaction, self-esteem, and enhances certain abilities [41][42][43][44]. When comparing our findings with previous studies, as we have just seen, there is alignment with existing literature suggesting a significant relationship between education and well-being in old age.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, lifelong learning has been associated with the reduction of cognitive decline in older adults, even with short participation in cognitively stimulating activities [40]. Several studies have shown that computer use increases social interaction, self-esteem, and enhances certain abilities [41][42][43][44]. When comparing our findings with previous studies, as we have just seen, there is alignment with existing literature suggesting a significant relationship between education and well-being in old age.…”
Section: Discussionsupporting
confidence: 87%